TREATMENT OF ENDOMETRIOID OVARIAN CYSTS CONCERNING FERTILITY: A REVIEW OF MODERN METHODS - Айзикович, Борис Исаевич; Зотов, Семен Вадимович; Кулешов, Виталий Михайлович; Мотырева, Полина Юрьевна; Филимонов, Сергей Николаевич; Лихачева, Виктория Васильевна (Mother and Baby in Kuzbass, 2021)
To date, the question of choosing the optimal treatment for endometrioid cysts in infertile women remains relevant. The ovarian reserve of such women is influenced by both the endometrioma itself and the surgery to remove it. This paper provides an analysis of the literature and an overview of modern approaches to the treatment of endometrioid ovarian cysts concerning preserving or restoring fertility. The endometrioma influence on the ovarian anatomy and physiology is considered. The comparison of the surgical approach with minimally invasive techniques: aspiration, sclerotherapy of endometrioid cysts is provided. Attention is paid to the effectiveness of assisted reproductive technology in patients after the endometrioma treatment by different methods.
Keywords: endometrioma; endometriosis; ovarian reserve; infertility; in vitro fertilization; cystectomy; sclerotherapy; cyst aspiration